A METAPHOR: DOES COVID-19 IS AN OBSTACLE FOR ADOLESCENT ATHLETES? - Baykose, Nazmi; Ceylan, Gizem; Yazici, Atakan (Int Journal Lifescience & Pharma Research, 2021)
The aim of this study is to determine the perceptions of adolescent athletes regarding the concept of 'covid-19' with the help of metaphor. Participants of the study composed of 95 female and 60 males total 155 athletes (X-Age = 13,26 +/- 1,66 years) from different sports branches who live in a various province in Turkey. In the research, a metaphor form was prepared as a data collection tool to determine the participants' perceptions of the concept of COVID-19. According to form is COVID-19 .......... from the participants; Because ........ they were asked to complete the sentence. In research collected metaphors was used as descriptive tools that qualitative research model content analysis used. The research data reliability was found that 94%. The findings demonstrated participants produce 52 metaphor. The metaphors collected under 4 categories. These metaphors were collected in 4 categories. According to the metaphors, it was determined that the participants mostly developed metaphors related to the concept of covid-19 in the categories of social effects and psychological effects, followed by health effects and physical effects. The most metaphors produced by the participants were listed as restraint, imprisonment, not being free, boredom, illness, inaaction, death and virus. Result of this study determined that participants used vivid, lifeless, abstract and concrete metaphors for covid-19. In this study, results demonstrated that adolescent athletes define, perceive and commodify Covid-19 as a concept that completely changes the routine of their lives and affects their lives in terms of physical, psychological, social and health.
Keywords: Covid-19; Adolescent Athletes; Metaphor; Qualitative Research Method